(untitled) (World Bulletin of Public Health, 2025)
The thymus and spleen are key organs of the immune system that ensure coordination between the central and peripheral components of immunogenesis. Dysfunction of one of these organs may lead to systemic rearrangement of immune homeostasis. Objective. To identify morphological and morphometric features of the thymus in clinically healthy animals after splenectomy. Materials and Methods. The study was conducted on 40 adult Wistar rats divided into control and experimental groups. Splenectomy was performed under aseptic conditions. The thymus was collected on postoperative days 14 and 30. Histological and morphometric methods were applied, followed by statistical analysis.